Effect of remote ischaemic conditioning on left ventricular function in ST-segment elevation myocardial infarction patients: The CONDI-2 echocardiographic sub-study - Wood, Gregory; Johnsen, Pia Hedegaard; Pedersen, Anders Lehmann Dahl; Frederiksen, Christian Alcaraz; Poulsen, Steen Hvitfeldt; Bøtker, Hans Erik; Kim, Won Yong (Frontiers in Cardiovascular Medicine, 2023)
Background Remote ischaemic conditioning (RIC) applied to the arm by inflation and deflation of a pneumatic cuff has been shown to reduce myocardial infarct size in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention (PPCI). However, the effect of RIC on left ventricular ejection fraction (LVEF) following infarct healing remains unknown. Objective To investigate whether RIC applied in the ambulance before PPCI can improve left ventricular (LV) function in STEMI patients 3 months following infarction. Methods Echocardiography was performed in a total of 694 patients from the CONDI-2 study a median of 112 days (IQR 63) after the initial admission. LVEF and LV end-diastolic and end-systolic volumes were calculated using the modified Simpsons biplane method of discs. LV global longitudinal strain (GLS) was estimated using 2-dimensional cine-loops with a frame rate >55 frames/second, measured in the three standard apical views. Results There was no difference in the measured echocardiographic parameters in the RIC group as compared to the control group, including LV EF, LV GLS, tricuspid annular plane systolic excursion or left ventricular volumes. In the control group, 32% had an ejection fraction < 50% compared to 37 % in the RIC group (p=0.129). Conclusion In this largest to date randomized imaging study of RIC, RIC as an adjunct to PPCI was not associated with a change in echocardiographic measures of cardiac function compared to standard PPCI alone.